Simulation and optimization of Lattice Mismatched InGaAs Thermophotovoltaic Cell - Sebastian S.J.; Rashid W.E.S.W.A.; Lee H.J.; Jamaludin M.Z.; Ker P.J.; Gamel M.M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Thermophotovoltaic (TPV) system harvests heat from thermal radiation where the photons are absorbed by a photovoltaic (PV) cell device and generates electrical energy. InGaAs is one of the popular III-V semiconductors material and has a great potential to be an efficient TPV cell if further optimization and improvements are made. In this paper, In0.68 Ga0.32 As with bandgap energy of 0.6 eV and cut-off wavelength at 2.1 ?m is modeled and optimized using TCAD simulation software. InAsP buffer layers were incorporated to reduce 1.1% lattice-matched effect between the device layer and lnP substrate. The cell's base and emitter layers were optimized by varying the thickness and the doping concentration of the cell layer individually under 1400 K blackbody spectrum. The optimization of emitter thickness and base doping concentration significantly contribute to a higher cell performance. An emitter thickness of 0.06 ?m contributes to an efficiency (?) of 25.55% while a base doping concentration of 1 1016 cm-3 recorded 23.08% of ?. 2020 IEEE.